1983
DOI: 10.3109/00016348309155779
|View full text |Cite
|
Sign up to set email alerts
|

Supra Vaginal Uterine Amputation VS. Hysterectomy

Abstract: Postoperative symptoms of hysterectomy have received relatively little attention. In the present study, the first author has personally interviewed and examined 105 abdominal hysterectomy patients and 107 patients with supravaginal uterine amputation preoperatively and 6 weeks, 6 months and 12 months postoperatively. Participation in the follow-up study was 99.5% (211/212) at one year. This paper deals with the effects of the two operations on libido and the frequency of orgasms. In the statistical analysis, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
16

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(106 citation statements)
references
References 12 publications
3
86
1
16
Order By: Relevance
“…This procedure has gained popularity among women and doctors because of reports indicating potential advantages. [2][3][4][5] It also seems to be a mode of hysterectomy that is preferred and recommended by gynaecologists to women with certain gynaecological disorders. [6][7][8] Relatively few randomised trials have compared subtotal abdominal hysterectomy (SH) and total abdominal hysterectomy (TH).…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has gained popularity among women and doctors because of reports indicating potential advantages. [2][3][4][5] It also seems to be a mode of hysterectomy that is preferred and recommended by gynaecologists to women with certain gynaecological disorders. [6][7][8] Relatively few randomised trials have compared subtotal abdominal hysterectomy (SH) and total abdominal hysterectomy (TH).…”
Section: Introductionmentioning
confidence: 99%
“…Kilkku dice que tras la histerectomía la libido no cambia pero la capacidad para alcanzar el orgasmo disminuye 58 , algo que tampoco es acorde con nuestros hallazgos según el test FSM ® , pero sí hemos visto que parte de las mujeres que consideran que su vida sexual empeora lo relacionan con menos orgasmos y menos intensidad en los mismos.…”
Section: Discussionunclassified
“…Puede ocurrir deterioro en la función sexual tras la cirugía. Las razones que pueden afectar a la sexualidad tras la histerectomía son: las consideraciones anatómicas como la cicatriz que queda en la vagina o la disrupción de nervios, la posible disminución en la sensibilidad de la vagina, el hecho de quitar el cérvix, el empeoramiento del orgasmo en aquellas mujeres con contracciones uterinas durante el mismo, las preocupaciones porque el útero pueda contribuir a aportar una sensación de bienestar y feminidad, etc 3,4,18,19,58 .…”
Section: Histerectomía Y Función Sexualunclassified
“…With regard to sexual outcome including coital frequency, desire, orgasm frequency, dyspareunia and overall sexual outcome, a systematic review of effect on sexual function following subtotal abdominal hysterectomy versus total abdominal hysterectomy identified four non-randomized studies, one of which showed that total abdominal hysterectomy had advantages over subtotal abdominal hysterectomy (20), two of which showed that subtotal abdominal hysterectomy had advantages over total abdominal hysterectomy with respect to sexual function (36,37). The remaining one, in addition to five randomized controlled trials showed no difference (20,(38)(39)(40)(41)(42).…”
Section: Anaesthesia-related Complicationsmentioning
confidence: 99%